Antibody Peptide Based Antifungal Immunotherapy - Magliani, Walter; Conti, Stefania; Giovati, Laura; Zanello, Pier Paolo; Sperindè, Martina; Ciociola, Tecla; Polonelli, Luciano (Frontiers in Microbiology, 2012)
We addressed the possibility that any fragment of the variable and constant regions may display antifungal (fungicidal and/or immunomodulatory) activity irrespective of the specificity for a given antigen or the isotype of the belonging antibody (Ab). Complementarity determining regions (CDRs)-based synthetic peptides of recombinant and monoclonal murine and human Abs directed to unrelated epitopes showed differential in vitro and/or in vivo antifungal activities, conceivably mediated by different mechanisms of action. Alanine substituted peptides obtained from fungicidal CDR sequences, and used as surrogates of natural point mutations, showed further differential increased, unaltered or decreased candidacidal activitiy. Candidacidal CDR-related peptides, which proved to be devoid of cytotoxicity on mammalian cells, showed to be characterized in solution by a peculiar self-aggregation-releasing property that could provide protection against proteases and a slow release of the active form over time. An immunomodulatory synthetic peptide related to a CDR proved to exert a therapeutic effect against systemic candidiasis without possessing direct candidacidal properties. Likewise CDR-related peptides, synthetic peptides with sequence identical to fragments putatively deriving from the cleavage of the constant region of Abs proved to display in vitro and/or in vivo fungicidal and/or immunomodulatory antifungal activity. These results open a new scenario about the possibility that Ab fragments may effectively influence the antifungal immune response in a way reminiscent of peptides of innate immunity. It is suggested, moreover, that immunoglobulins (Igs) may be sources of an unlimited number of sequences potentially active against fungal agents and related mycoses.